Hand Surgery in Saudi Arabia - Kattan, Abdullah E.; Al-Qattan, Mohammad M. (Journal of Hand and Microsurgery, 2020)
Hand surgery is a unique field that incorporates multiple specialties, aiming to provide the patient with a best possible functional and aesthetic results. Hand surgeons deal with different pathologies that require skills in several aspects of surgery. The field of hand surgery has evolved significantly over the past decades across the globe. This specialty has also been evolving in Saudi Arabia over the past 25 years. Some of the services offered to patients include specialized centers for brachial plexus, peripheral nerve, and pediatric hand surgery as well as centers for work-related hand injuries. There has also been significant contribution to the hand surgery literature from the hand surgeons working in Saudi Arabia, with hundreds of papers published in journals pertaining to hand surgery, orthopedic surgery, and plastic surgery, as well as the publication of several novel mutations causing congenital hand defects in journals concerned with genetics. The recent approval of a hand and microsurgery fellowship program in Saudi Arabia will also help boost this field in the country and the region.
Keywords: hand; surgery; Saudi Arabia